Statistical analysis of a noise measurements for the series of roro ships - Weryk, Mateusz (Archives of Acoustics, 2007)
The importance of noise and vibration measurements during the sea trials is significant, especiallynow when noise limits are getting more restrictive and ship-owners demand to obeythose noise limits. For a new-built vessels the normal procedure is to perform noise forecast atdesign stage. Taking into account weight limiting the passive noise insulation becomes a veryimportant issue, therefore in order to avoid solutions which are not effective one should baseon a realistic noise excitation data. Noise forecasts are mostly based on initial documentationand characteristics of main sources e.g. engines, generator sets, propellers etc, which are provided(measured or calculated) by manufacturers. Ship noise prediction might differ from realon-board noise situation. The question is what is a standard deviation between forecast andnoise measurement. Normally for noise prediction analysis the worst case scenario is takeninto account, so one can expect that real on-board noise levels will be lower then forecasted.However, when weight limits are taken into account in standard work case scenario the realon-board noise levels are more or less the same as forecasted. The question is how much is it“more or less”? Conducting the measurements onboard of a series of ships creates the convenientopportunity to perform statistical analysis of the results. The paper focuses on statisticalanalysis of noise measurements performed for the series of ro-ro ships.